Antioxidant and anti-aging enzyme activities of bioactive compounds isolated from selected Zingiberaceae plants - Rittipun Rungruang,; Wittawat Ratanathavorn,; Nattaporn Boohuad,; Orrapun Selamassakul,; Nattapon Kaisangsri, (Agriculture and Natural Resources, 2021)
Bioactive compounds and antioxidant and enzyme inhibition activity levels were evaluated for three plants in the Zingiberaceae family in Thailand. Quantification of the phenolic and curcumin contents revealed that the largest component of all extracts was phenolic compounds (213.16–317.64 mg/g extract). The major curcuminoids in Curcuma longa L., Curcuma aromatica Salisb. and Zingiber montanum (J.Koenig) Link ex A.Dietr. were bisdemethoxycurcumin (BDMC; 27.31 mg/g extract), curcumin (16.59 mg/g extract), and curcumin (0.12 mg/g extract), respectively. The extracts from C. longa, C. aromatica and Z. montanum all showed antioxidant activity that was assessed using 1,1-diphenyl-2-picrylhydrazyl radical 2,2-diphenyl-1-(2,4,6-trinitrophenyl) hydrazyl (DPPH•) and 2,2’-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS•+) radical scavenging assay. In addition, all extracts had copper chelating activity of more than 50%, with the extract from C. longa having the highest chelating activity (76.45%). All extracts from the three plants inhibited tyrosinase and elastase activity with half maximal inhibitory concentration values of 290.33–1,373.68 μg/mL and 69.61–3386.23 μg/mL, respectively. In addition, collagenase inhibition activity was observed in all extracts. The findings from this study showed that extracts from C. longa, C. aromatica and Z. montanum have potential antioxidant activity and can act as anti-tyrosinase, anti-collagenase and anti-elastase agents. The extracts could be further applied in cosmeceuticals as an active ingredient for anti-aging products.